Lactic Acid Bacteria Isolated from Cangkuak Riau: Characterization of Antibacterial Activity - Maslami, Vebera; Noersidiq, Azhary; Fahrullah, Fahrullah; Dani Putra, Endo Pebri; Nugraha, Aditya Wahyu; Utami, Wirawati Chandra; Mahendra, Khoiri (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
This paper reports on the Cangkuak from the fermentation of meat and bones using bamboo shoots, added rice and salt stored in a container (anaerobic conditions). The cangkuak was obtained from the Riau (Indonesia). The cangkuak may contain lactic acid bacteria (LAB), which are essential in the fermentation process. Most LAB is gram-positive bacteria with some health benefits, such as antibacterial. This study investigated the isolate and characterized LAB from cangkuak by an antibacterial activity test. The bacteria used Bacillus Cereus, S. Aureus, E. Colli, and Salmonella sp. Bacterial isolates were grown on MRS agar media, to which 0,5% CaCO3 was added and then purified using the streak method. The results obtained were pure isolates. The results of the cangkuak isolation showed 8 LAB isolates. The eight isolates were characterized by standard Bergey's manual of systemic bacteriology (genus Lactobacillus sp). Furthermore, an antibacterial test revealed differences in ineffectiveness against the inhibition zone. Cangkuak (CK) 3.1 isolate was most effective in inhibiting bacterial growth. The size of the inhibition zone for Aureus, E. Colli, and Salmonella sp. were 10.82 mm, 12.65 mm, and 12.29 mm, respectively. This result could indicate the presence of LAB isolates from fermented foods that have the potential to be antibacterial.